Cyber security and safety of nuclear power plant instrumentation and control systems - Yastrebenetsky, Michael 1934; Kharchenko, Vyacheslav 1952 (Advances in information security, privacy, and ethics (AISPE) Book series, 2020)
"This book examines methods of cyber security and safety in nuclear power plant instrumentation and control systems"